Marca própria compartilhada: a reconfiguração da concorrência varejista a partir das centrais de negócios - Lemos, Ana Claudia Moura (2012)
Food retailing in Brazil is the most noticeable segment in Brazilian economy, with a growth estimate of 8% in 2012, which denotes a highly attractive market, considering that the country’s growth expectancy is 2%, with a 5% inflation. Such development attracts international investors, making the big worldwide retailing networks arrive in the country through acquiring, merging or turning inviable the existence of small supermarkets, which, as a way to remain in the market, seek association to Business Centers. “SUPER REDE”, a Business Center from Ceará has national prominence, and is considered by “Associação Brasileira de Supermercados” – ABRAS (Supermarket Brazilian Association), as the largest Business Center in the country in terms of income for 03 consecutive years. One of the strategies adopted by SUPER REDE in its product mix selection is own branding. The present study’s main objective is to analyze the perception of SUPER REDE’s own brand based on the dimensions proposed by David Aaker towards Brand Loyalty, Perceived Quality, Brand Awareness and Brand Associations according to the consumer. The study is exploratory and descriptive, of a qualitative nature, with literature review of the transversal themes and data collection through structured questionnaires, with open and closed questions. Value perception is considered a factor with a strong effect in shopping decision. The results are relevant, as they show the importance, the interconnection and the effect of the dimensions in business, being a contribution both to the Academy and to Business Centers with an own brand.